Chemomechanical-force-induced folding–unfolding directly controls distinct fluorescence dual-color switching. Issue 36 (20th April 2017) - Chen, Jian; Ziegler, Adam W.; Zhao, Baoming; Wan, Wei; Li, Alexander D. Q.
Abstract : Molecular folding and unfolding switch fluorescence color from orange to green; this molecular actuation-induced fluorescence color switching is highly reversible and shows remarkable fatigue resistance. Abstract : Folding–unfolding imparts fluorescence dual color switching, thus a novel concept to switch fluorescence between two distinct colors while avoiding traditional bond rupturing and bond forming in photoswitching. Because folding and unfolding minimize the wear and tear on molecular structures, the new systems have excellent reversibility and fatigue resistance.